Awareness towards inheritance’s management in Islamic perspectives: a study among ACIS’s students in UiTM Puncak Alam / Siti Nur Nadhiha Zahari - Zahari, Siti Nur Nadhiha (2019)
This research is to investigate the awareness towards management of inheritance in Islamic perspectives among ACIS‟s students in UiTM Puncak Alam. Increasing values of unclaimed inheritance property and frozen assets have emerged as one of the long-standing issues among Muslims in Malaysia and need attention. In 2011, the New Straits Times reported that the total amount of money that remained to be claimed by the rightful beneficiaries stood at RM4.53 billion. It's important for families to prepare a will or inform their loved ones of assets they own to avoid the issue of unclaimed assets and money. The objectives of this study are to justify the understanding on awareness among ACIS‟s students towards inheritance‟s management in Islamic perspectives, to examine the level of awareness among ACIS‟s students in UiTM Puncak Alam towards inheritance‟s management in Islamic perspectives and also to analyse the appropriate ways for ACIS‟s students in UiTM Puncak Alam to be knowledgeable towards inheritance‟s management in Islamic perspectives. Thus, to analyse this research Statistical Package for the Social Science (SPSS) Version is used to measure the validity. The findings of this study indicate that ACIS‟s students in UiTM Puncak Alam Staff have a great awareness of management of inheritance. However, there is a great opportunity for improvement in the future with regards to the awareness on inheritance‟s management in Islamic perspectives.